386 Risk factors comprehensive geriatric assessment for early death in elderly patients with gynecological cancer. A prospective cohort study. (18th September 2019) - Sales, J; Azevedo, C; santos, C; sales, L; Bezerra, M; Bezerra, G; cavalcanti, Z; Mello, MJ
Abstract : Objectives: To determine risk factors for early death identified the Comprehensive Geriatric Assessment (CGA) in elderly patients with gynecological cancer (EPGC). Methods: Prospective cohort study. Participants with a recent diagnosis of cancer were from eight community hospitals and one cancer center in Northeast Brazil and were recruited during their first medical appointment at the outpatient oncologic clinic. A basal CGA was done before the treatment decision (ADL, Charlson Comorbidity Index- CCI, Karnofsky Performance status – KPS, GDS15, IPAQ, MMSE, MNA, MNA-SF, PS, PPS, Polipharmacy, TUG). During the follow up of 12 months, information about the treatments performed, the targeted interventions and early death was collected. Overall survival was estimated using the Kaplan–Meier method, and survival curves were compared using the Log rank test for categorical variables. A multivariate Cox proportional hazards model was used. Results: From 2015–2017, 84 EPGC, mean age 69, 6±7, 9; range 60–96), were enrolled, 25% were metastatic disease. tumor site: 40, 4% cervical uterine, 36, 9%endometrial, 20, 2% ovary and 2, 3 vulva. Nine (10.7%) ECP died in less than 12 months of follow-up.In our multivariate model, controlled by age, site of cancer and cancer stage, the remaining significant risk factors were malnutrition/nonutrition determined by MNA-SF (HR 3.70, 95% CI 1.81–5.99, p<0.001), Katz index (HR 3.60, CI 1.56–3.81, p<0.001) CCI >2 (HR 2, 74, CI 1.0.74–10.20, p=0.013) and Polipharmacy (HR 2.65, CI 0.71–9.81, p<0.001). Conclusions: The CGA at admission identified risk factors (Nutritional risk, polypharmacy, functionality for Katz index and comorbidity index) for premature death in EPGC. They can help to plan a personalized care.